Dental resin-permeable ceramic and preparation method thereof
Through the unsilanized barium glass ceramic material and the temperature isostatic pressing method, the problem of mismatch between the aesthetic properties of dental restoration materials and the complex and time-consuming process is solved, and the high mechanical properties of dental resin permeable ceramic materials are achieved It takes into account both aesthetic performance and is suitable for large-scale production.
Patent Information
- Application Number
- CN202411371686.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
AI Technical Summary
The aesthetic properties of existing dental restoration materials do not match the natural teeth, and the traditional penetration ceramic process is complex and time-consuming, which affects the mechanical properties and bending strength of the materials.
The barium glass ceramic material without silanization is sintered to form a porous ceramic blank, and the resin is penetrated into the ceramic by temperature isostatic pressing, and the resin is cured with a resin matrix without initiator, simplifying the process and improving the permeability efficiency.
The prepared dental resin permeable ceramic materials are similar to natural teeth in aesthetic properties, have high mechanical properties, and have bending strength of more than 250MPa. The process is simple and suitable for large-scale production.
Smart Images

Figure CN119191684A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of dental composite materials, and specifically relates to a dental resin-infiltrated ceramic and a preparation method thereof. Background Art
[0002] With the development of digital technology, computer-aided design / computer-aided manufacturing (CAD / CAM) has gradually replaced manual methods and has been widely used in the field of restoration manufacturing. With the development of high-strength ceramic materials such as zirconia and alumina, CAD / CAM technology has been further applied and developed in the oral field. However, the brittleness of ceramic materials is still its inherent weakness, and ceramic materials have higher elastic modulus and hardness than the opposing teeth, which causes a certain degree of wear on the opposing teeth and damages the health of the opposing teeth. At present, the use of CAD / CAM technology to make composite restorations has also begun to attract more and more attention. Studies have found that composite materials have good toughness, machinability, and wear resistance, can shorten processing time and reduce tool wear, and composite resins have certain aesthetics and no wear on the opposing teeth. They are currently commonly used restoration materials for tooth defects. However, composite resins have low strength and wear resistance, and have certain polymerization shrinkage, which affects the tightness of the restoration and becomes a limiting factor affecting its further use. Therefore, it is of great clinical significance to prepare a dental restoration bionic material that has the advantages of both ceramic and resin materials and matches the various properties of natural tooth tissue.
[0003] Many traditional processes use ceramic components such as zirconium oxide or aluminum oxide to press and sinter to obtain a porous ceramic network structure. After the porous ceramic network is silanized, it is infiltrated with a resin monomer and then thermally cured to obtain a cross-linked structure of resin and ceramic, that is, a resin-infiltrated ceramic composite material. However, the aesthetic properties of infiltrated ceramics made of materials such as zirconium oxide and aluminum oxide are poor, and they do not match the refractive index and light transmittance of teeth, and are not suitable for making dental restorations.
[0004] The traditional process also discloses a machinable resin-infiltrated glass-ceramic material for dental restoration and a preparation method thereof. The method uses silanized barium glass powder as a raw material, and after drying, the mixed powder is pressed into a porous block ceramic body without sintering. The resin monomer is directly infiltrated into the porous ceramic, and the infiltrated ceramic is obtained after curing. Although this method has a certain strength for making infiltrated ceramics, the method uses a vacuum infiltration method, which needs to be repeated at least 3 times and each time is greater than 30 minutes, which increases the infiltration time and is complicated to operate. In addition, the silanized barium glass powder cannot be sintered to form a cross-linked structure with higher strength. Non-sintering will lead to uneven distribution of material pores, which will lead to pore closure after warm isostatic pressing, reduce the resin permeability, and thus have a certain impact on the bending strength and aesthetic properties of the material.
[0005] In addition, the traditional process also discloses a method for preparing a high-hardness, wear-resistant resin-infiltrated ceramic composite material, which uses a silicate containing potassium and sodium aluminum silicate as a raw material, sintering the ceramic block at 600-800°C to form a cross-linked network, and then infiltrating and curing the resin. The sintering temperature is reduced and the hardness of the material is increased, but the bending strength of the material is relatively reduced. The final bending strength of the infiltrated ceramic is less than 180MPa, which has great limitations in dental applications. And this method also uses a vacuum infiltration method for resin infiltration, which increases the infiltration time and operation steps.
[0006] Therefore, there is a need for a resin-infiltrated ceramic material that has a simple preparation process, is less time-consuming, has a simple infiltration method, and can have aesthetic properties similar to those of natural teeth while also having high mechanical properties. Summary of the invention
[0007] Based on this, it is necessary to provide a resin-infiltrated ceramic material and a preparation method thereof in one embodiment of the present application. The method has a simple process, consumes less time, and has a simple infiltration method. A resin-infiltrated ceramic composite material is prepared that has aesthetic properties similar to natural teeth and has higher mechanical properties.
[0008] The technical solutions include the following:
[0009] A method for preparing dental resin-infiltrated ceramics comprises the following steps:
[0010] The ceramic material and the binder are mixed in a solvent and then dry-pressed to prepare a ceramic block; wherein the ceramic material comprises barium glass that has not been silanized;
[0011] Sintering the ceramic block to prepare a porous ceramic body;
[0012] Performing a silanization treatment on the porous ceramic body to prepare a modified porous ceramic body;
[0013] The porous ceramic body is immersed in an acrylic monomer resin mixture containing an initiator, and infiltrated by warm isostatic pressing; and
[0014] The resin-infiltrated ceramic body is cured in a resin matrix without an initiator to prepare resin-infiltrated ceramics.
[0015] In one embodiment, the sintering step includes heating the temperature to 500° C. to 650° C. at a heating rate of 2° C. / min to 3° C. / min and keeping the temperature for 3 h to 4 h.
[0016] In one embodiment, the porosity of the porous ceramic body is 30% to 45%.
[0017] In one embodiment, the silanization step includes impregnating the porous ceramic body with a silane coupling agent solution under vacuum conditions.
[0018] In one embodiment, the silane coupling agent solution comprises ethanol, water and a silane coupling agent, and the mass ratio of the ethanol, water and the silane coupling agent is (6-8): (2-4): (0.5-1).
[0019] In one embodiment, the pH value of the water is 3-5.
[0020] In one embodiment, the vacuum condition includes a vacuum degree of -0.1 MPa to -0.8 MPa.
[0021] In one embodiment, the immersion time is 1 h to 2 h.
[0022] In one embodiment, the dipping further includes a drying process.
[0023] In one embodiment, the acrylic monomer resin mixture includes at least two of bisphenol A propylene glycol dimethacrylate, triethylene glycol dimethacrylate, methacrylate and urethane dimethacrylate.
[0024] In one embodiment, the acrylic monomer resin mixture is triethylene glycol dimethacrylate and urethane dimethacrylate.
[0025] In one embodiment, the mass ratio of the triethylene glycol dimethacrylate to the urethane dimethacrylate is (7-3): (3-7).
[0026] In one embodiment, the initiator is selected from peroxides and / or azo compounds.
[0027] In one embodiment, the peroxide comprises benzoyl peroxide (BPO).
[0028] In one embodiment, the initiator content is 0.1 wt % to 0.5 wt % of the acrylic monomer resin mixture.
[0029] In one embodiment, the warm isostatic pressing parameters include a temperature of 30° C. to 60° C. and a pressure of 50 MPa to 150 MPa.
[0030] In one embodiment, the penetration time is 1 h to 3 h.
[0031] In one embodiment, the resin-infiltrated ceramic body is cured in a resin matrix without an initiator by warm isostatic pressing.
[0032] In one embodiment, the resin matrix without initiator is the acrylic monomer resin mixture defined above.
[0033] In one embodiment, the warm isostatic pressing parameters include a temperature of 100° C. to 150° C. and a pressure of 80 MPa to 200 MPa.
[0034] In one embodiment, the barium glass without silanization treatment has a particle size ranging from 0.1 μm to 3 μm, a normal distribution of the particle size, and an average particle size of 0.6 μm to 0.8 μm.
[0035] In one embodiment, the amount of the adhesive added is 2wt% to 9wt% of the ceramic material.
[0036] In one embodiment, the adhesive comprises polyethylene glycol.
[0037] Optionally, the solvent is acidic deionized water.
[0038] In one embodiment, dry pressing includes compression molding and cold isostatic pressing.
[0039] Optionally, the compression molding pressure is 6 MPa to 12 MPa.
[0040] Optionally, the pressure of cold isostatic pressing is 160 MPa to 220 MPa.
[0041] In one embodiment, the mixing method includes ball milling.
[0042] Optionally, after mixing, the method further includes drying the obtained slurry and grinding it into powder.
[0043] The dental resin-infiltrated ceramics prepared by the preparation method.
[0044] Compared with the traditional technology, this application has the following beneficial effects:
[0045] The present application uses barium glass powder that has not been silanized, and the sintering temperature is easy to achieve, and can be used for large-scale production. The porosity is 30-45%, which increases the resin penetration efficiency. The resin is infiltrated into the porous ceramic body in combination with warm isostatic pressing. The resin viscosity is low at the set temperature, which is easier to penetrate, and a high-pressure method is used for penetration, so that the force in all directions is uniform. There are fewer pores after penetration. Compared with the vacuum infiltration method, the process is simple, and it can be used for large-scale production. There is no need for multi-step penetration, and it is cured in a resin matrix environment without an initiator, reducing the tiny cracks caused by polymerization shrinkage in the infiltrated ceramic. The resin infiltrated ceramic produced by the present application saves time, and the infiltrated resin obtained by this method has enhanced material mechanical properties. The dental resin infiltrated ceramic composite material produced by the present application has a bending strength of more than 250MPa, which has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0047] Figure 1 For comparative example 2, the infiltration ceramic was prepared by vacuum infiltration method;
[0048] Figure 2 In Example 1, infiltrated ceramics were prepared using warm isostatic pressing. DETAILED DESCRIPTION
[0049] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0051] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0052] An embodiment of the present application provides a method for preparing dental resin-infiltrated ceramics. The inorganic components of the method are selected from barium glass ceramic particles that have not been silanized and have a gradient particle size range. They can be sintered to form a network structure with a certain structure to provide a certain strength for the infiltrated ceramics. In addition, the present application excludes the vacuum infiltration method for resin infiltration and selects the warm isostatic pressing method to infiltrate the resin monomer into the ceramic network, thereby reducing the infiltration time, simplifying the infiltration process, making the resin infiltrate evenly in the ceramic network, and increasing the mechanical properties of the infiltrated ceramic material.
[0053] Specifically, the following steps S1 to S5 are included:
[0054] Step S1, mixing ceramic material and adhesive in a solvent and dry pressing the mixture to prepare a ceramic block.
[0055] In one specific example, the ceramic material includes unsilanized barium glass.
[0056] In a specific example, the particle size of the un-silanized barium glass ceramic powder ranges from 0.1 μm to 3 μm, the particle size is normally distributed, and the average particle size is 0.6 μm to 0.8 μm. Optionally, the average particle size is 0.6 μm, 0.7 μm or 0.8 μm.
[0057] In one specific example, the adhesive includes polyethylene glycol.
[0058] In a specific example, the amount of adhesive added is 2wt% to 9wt% of the ceramic material, and optional values include but are not limited to 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or 9wt%.
[0059] In one specific example, the solvent is acidic deionized water.
[0060] In one specific example, the mixing method includes ball milling.
[0061] In a specific example, the ball milling step includes: adding ceramic material, adhesive and solvent into a ball milling jar for ball milling. Optionally, the ball milling jar is made of zirconium oxide, polyurethane or polyethylene; Optionally, the grinding balls are agate or zirconium oxide grinding balls.
[0062] In a specific example, the ball milling speed is 600 r / min to 800 r / min, and the time is 1 to 3 hours.
[0063] In a specific example, the ball milling mixing further includes the steps of drying the slurry and grinding it into powder.
[0064] In a specific example, the drying temperature is 50° C. to 60° C., and the drying time is 12 h to 24 h.
[0065] In a specific example, dry pressing includes compression molding and cold isostatic pressing. Optionally, the pressure of compression molding is 6MPa to 12MPa; the pressure of cold isostatic pressing is 160MPa to 220MPa.
[0066] In a specific example, the ground powder is sequentially molded and cold isostatically pressed to form a ceramic block.
[0067] Step S2, sintering the ceramic block to prepare a porous ceramic body.
[0068] In a specific example, the sintering step includes heating the temperature to 500° C. to 650° C. at a heating rate of 2° C. / min to 3° C. / min, and keeping the temperature for 3 h to 4 h.
[0069] The heating rate and sintering temperature affect the porosity of porous ceramics. The heating rate is 2℃ / mi~3℃ / min to 500℃~650℃ and kept for 3h~4h to ensure the porosity of porous ceramics is 30%~45%.
[0070] In the above sintering temperature of 500° C. to 650° C., the optional values include but are not limited to 500° C., 550° C., 600° C., 650° C. or any range between the two values.
[0071] Step S3, performing silanization treatment on the porous ceramic body to prepare a modified porous ceramic body.
[0072] In a specific example, the silanization step includes impregnating the porous ceramic body with a silane coupling agent solution under vacuum conditions.
[0073] In a specific example, the silane coupling agent solution contains ethanol, water and silane coupling agent in a mass ratio of (6-8):(2-4):(0.5-1), and optional values include but are not limited to 6:2:0.5, 6:2:1, 6:4:0.5, 6:4:1, 8:2:0.5, 8:2:1, 8:4:0.5 or 8:4:1.
[0074] In a specific example, the water is ionized water with a pH value of 3-5.
[0075] In a specific example, ethanol, water and silane coupling agent are stirred and mixed to prepare a silane coupling agent solution. Optionally, the stirring speed is 600 r / min to 800 r / min, and the stirring time is 1 h to 2 h.
[0076] In a specific example, the vacuum condition includes a vacuum degree of -0.1 MPa to -0.8 MPa.
[0077] In a specific example, the immersion time is 1 h to 2 h.
[0078] In a specific example, the dipping process further includes a drying process. Optionally, the drying temperature is 50° C. to 60° C., and the drying time is 12 hours to 24 hours.
[0079] Step S4, performing resin infiltration on the modified porous ceramic body by warm isostatic pressing.
[0080] In a specific example, the resin infiltration includes immersing the modified porous ceramic body in an acrylic monomer resin mixture containing an initiator, and performing the infiltration under warm isostatic pressing.
[0081] In a specific example, the acrylic monomer resin mixture includes at least two of bisphenol A glycerol dimethacrylate, triethylene glycol dimethacrylate, methacrylate, and urethane dimethacrylate.
[0082] Preferably, the acrylic monomer resin mixture is triethylene glycol dimethacrylate and urethane dimethacrylate.
[0083] Preferably, the mass ratio of triethylene glycol dimethacrylate to the urethane dimethacrylate is (7-3):(3-7), and optional values include but are not limited to 7:3, 6:4, 5:5, 4:6 or 3:7.
[0084] In a specific example, the initiator is selected from peroxides and / or azo compounds. Optionally, the peroxide includes benzoyl peroxide. Optionally, the initiator is benzoyl peroxide.
[0085] In a specific example, the initiator content is 0.1 wt% to 0.5 wt% of the acrylic monomer resin mixture, and optional values include but are not limited to 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt% or 0.5 wt%.
[0086] In a specific example, in a warm isostatic press, the penetration temperature is 30°C to 60°C, and optional values include but are not limited to 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or a range between any two values; the penetration pressure is 50MPa to 150MPa, and optional values include but are not limited to 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 120MPa, 140MPa, 150MPa, or a range between any two values; the penetration time is 1h to 3h, and optional values include but are not limited to 1h, 2h, 3h, or a range between any two values.
[0087] Step S5, curing the resin-infiltrated ceramic body in a resin matrix without an initiator to prepare a resin-infiltrated ceramic.
[0088] In one specific example, the resin-infiltrated ceramic body is cured in a resin matrix without an initiator using warm isostatic pressing.
[0089] In a specific example, the resin matrix without the initiator has the same composition as the acrylic monomer resin mixture in the above step S4.
[0090] In a specific example, the warm isostatic pressing parameters include a temperature of 100°C to 150°C, with optional values including but not limited to 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, and a pressure of 80MPa to 200MPa, with optional values including but not limited to 80MPa, 90MPa, 100MPa, 110MPa, 120MPa, 150MPa, 180MPa or 200MPa.
[0091] One embodiment of the present application provides a dental resin-infiltrated ceramic prepared by the above preparation method. The resin-infiltrated ceramic has a high bending strength of 177 MPa to 301 MPa and a Vickers hardness of 2.8 GPa to 4.2 GPa, which is between the hardness of enamel (2.7 GPa to 6.4 GPa) and dentin (0.12 GPa to 0.67 GPa).
[0092] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0093] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.
[0094] The barium glass in the following examples is barium glass that has not been subjected to silanization treatment and can be purchased commercially.
[0095] Example 1
[0096] This embodiment provides a dental resin-infiltrated ceramic and a preparation method thereof, the preparation method comprising the following steps:
[0097] Weigh 20g of barium glass powder and 0.6g of polyvinyl alcohol and add them into a ball mill, then add 100ml of deionized water with a pH value of 3, and ball mill at a speed of 800r / min for 2h. Pour out the slurry and place it in an oven at 50℃ for 12h, then take it out and grind it to obtain a powder. The powder is molded at a pressure of 10MPa, and cold isostatically pressed at a pressure of 200MPa for 90s to obtain a ceramic block. The ceramic block is placed in a sintering furnace and heated to 500℃ at a rate of 2℃ / min and kept warm for 4h to obtain a porous ceramic green body.
[0098] Take 80g of ethanol, 20g of deionized water and 5g of silane coupling agent (KH-570) and put them into a beaker. Use a magnetic stirrer to stir for 1h to mix evenly. Put the porous ceramic body into it to ensure that it is completely immersed. Put it into a vacuum box for vacuum impregnation with a vacuum degree of -0.1MPa. Take it out after impregnation for 1h and put it into a 50℃ oven for 24h before taking it out.
[0099] 70 g of urethane dimethacrylate (UDMA), 30 g of triethylene glycol dimethacrylate (TEGDMA) and 0.2 g of BPO were mixed in a mass ratio, and ultrasonicated for 30 min to obtain an acrylic monomer resin mixture containing an initiator.
[0100] The porous ceramic body was placed in a tin foil bag, an acrylic monomer resin mixture containing an initiator was added to immerse the porous ceramic body, and then sealed with a vacuum sealer. The body was placed in a warm isostatic press and infiltrated at 50°C and 100 MPa for 2 h. The ceramic block was taken out and cured at 120°C and 120 MPa for 4 h in an environment of 70 g of urethane dimethacrylate (UDMA) and 30 g of triethylene glycol dimethacrylate (TEGDMA) to obtain an infiltrated ceramic material 1.
[0101] Example 2
[0102] In this embodiment, an infiltration ceramic material 2 is prepared. The preparation method is substantially the same as that of embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 550°C.
[0103] Example 3
[0104] In this embodiment, an infiltrated ceramic material 3 is prepared. The preparation method is substantially the same as that of embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 600°C.
[0105] Example 4
[0106] In this embodiment, an infiltrated ceramic material 4 is prepared. The preparation method is substantially the same as that of Embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 650°C.
[0107] Example 5
[0108] In this embodiment, an infiltration ceramic material 5 is prepared by a preparation method substantially the same as that of embodiment 1, except that in this embodiment, 60 g of urethane dimethacrylate (UDMA), 40 g of triethylene glycol dimethacrylate (TEGDMA) and 0.2 g of BPO are mixed in a mass ratio.
[0109] Example 6
[0110] In this embodiment, an infiltration ceramic material 6 is prepared by a preparation method substantially the same as that of embodiment 1, except that in this embodiment, 50 g of urethane dimethacrylate (UDMA), 50 g of triethylene glycol dimethacrylate (TEGDMA) and 0.2 g of BPO are mixed in a mass ratio.
[0111] Example 7
[0112] In this embodiment, an infiltration ceramic material 7 is prepared by a preparation method substantially the same as that of embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 550°C; and 60g of urethane dimethacrylate (UDMA), 40g of triethylene glycol dimethacrylate (TEGDMA) and 0.2g of BPO are mixed in a mass ratio.
[0113] Example 8
[0114] In this embodiment, an infiltration ceramic material 8 is prepared by a preparation method substantially the same as that of Embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 550°C; and 50 g of urethane dimethacrylate (UDMA), 50 g of triethylene glycol dimethacrylate (TEGDMA) and 0.2 g of BPO are mixed in a mass ratio.
[0115] Example 9
[0116] In this embodiment, an infiltration ceramic material 9 is prepared by a preparation method substantially the same as that of embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 600°C; and 60g of urethane dimethacrylate (UDMA), 40g of triethylene glycol dimethacrylate (TEGDMA) and 0.2g of BPO are mixed in a mass ratio.
[0117] Example 10
[0118] In this embodiment, an infiltration ceramic material 10 is prepared by a preparation method substantially the same as that of Embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 600°C; and 50g of urethane dimethacrylate (UDMA), 50g of triethylene glycol dimethacrylate (TEGDMA) and 0.2g of BPO are mixed in a mass ratio.
[0119] Embodiment 11
[0120] In this embodiment, an infiltration ceramic material 11 is prepared by a preparation method substantially the same as that in Embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 650°C; and 60 g of urethane dimethacrylate (UDMA), 40 g of triethylene glycol dimethacrylate (TEGDMA) and 0.2 g of BPO are mixed in a mass ratio.
[0121] Example 12
[0122] In this embodiment, an infiltration ceramic material 12 is prepared by a preparation method substantially the same as that of Embodiment 1, except that the ceramic body of this embodiment is sintered at a temperature of 600°C; and 50 g of urethane dimethacrylate (UDMA), 50 g of triethylene glycol dimethacrylate (TEGDMA) and 0.2 g of BPO are mixed in a mass ratio.
[0123] Comparative Example 1
[0124] In this comparative example, comparative material 1 was prepared. The preparation method was substantially the same as that of Example 1, except that the ceramic body of this comparative example was directly infiltrated with resin without being sintered.
[0125] Comparative Example 2
[0126] In this comparative example, comparative material 2 was prepared. The preparation method was roughly the same as that of Example 1, except that the resin infiltration method was vacuum infiltration: during the infiltration, the porous ceramic body was placed in a beaker, and an acrylic monomer resin mixture with an initiator was added to immerse the porous ceramic body. A vacuum drying oven was used for infiltration at 50°C and -0.1 MPa for 4 hours.
[0127] Comparative Example 3
[0128] In this comparative example, comparative material 3 was prepared by the same preparation method as in Example 1, except that after the resin was infiltrated by warm isostatic pressing, the ceramic block was taken out and dried, and then directly put into a tin paper bag and cured by warm isostatic pressing at 120°C and 120 MPa for 4 hours to obtain a comparison.
[0129] Comparative Example 4
[0130] In this comparative example, comparative material 4 was prepared. The preparation method was substantially the same as that of Example 1, except that in this comparative example, the barium glass powder was replaced with zirconium oxide.
[0131] Test example
[0132] This test example tests the bending strength and Vickers hardness of the materials prepared in the examples and comparative examples. Wherein: a universal testing machine (AGS, Shimadzu, Japan) is used to test the bending strength. A three-point bending test is used, the loading rate is 1 mm / min, and the sample size is 18×4×2 mm. A Vickers hardness tester (VH1150, Wilson, USA) is used to test the hardness, and the sample size is 6 mm×3 mm×25 mm.
[0133] The test results are shown in Table 1.
[0134] Table 1
[0135]
[0136] The infiltrated ceramic materials of Examples 1 to 12 of the present application have high bending strength, ranging from 177 MPa to 301 MPa, and Vickers hardness ranging from 2.8 GPa to 4.2 GPa, which is between enamel (2.7 GPa to 6.4 GPa) and dentin (0.12 GPa to 0.67 GPa). Among them, the bending strength of Example 8 is the best, exceeding 300 MPa, meeting the requirements for the production of oral restorations.
[0137] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0138] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.
Claims
1. A method for preparing dental resin-infiltrated ceramics, characterized in that: The following steps are involved: The ceramic material and the binder are mixed in a solvent and then dry-pressed to prepare a ceramic block; wherein the ceramic material comprises barium glass that has not been silanized; Sintering the ceramic block to prepare a porous ceramic body; Performing a silanization treatment on the porous ceramic body to prepare a modified porous ceramic body; The porous ceramic body is immersed in an acrylic monomer resin mixture containing an initiator, and infiltrated by warm isostatic pressing; and The resin-infiltrated ceramic body is cured in a resin matrix without an initiator to prepare resin-infiltrated ceramics.
2. The preparation method according to claim 1, characterized in that: The sintering step includes heating the temperature to 500°C to 650°C at a heating rate of 2°C / min to 3°C / min and keeping the temperature for 3h to 4h; Optionally, the porosity of the porous ceramic body is 30% to 45%.
3. The preparation method according to claim 1 or 2, characterized in that: The silanization treatment step includes impregnating the porous ceramic body with a silane coupling agent solution under vacuum conditions; Optionally, the silane coupling agent solution comprises ethanol, water and a silane coupling agent, and the mass ratio of the ethanol, water and the silane coupling agent is (6-8): (2-4): (0.5-1); Optionally, the pH value of the water is 3 to 5; Optionally, the vacuum condition includes a vacuum degree of -0.1MPa to -0.8MPa; Optionally, the immersion time is 1 h to 2 h; Optionally, a drying process is further included after the impregnation.
4. The preparation method according to claim 1 or 2, characterized in that: The acrylic monomer resin mixture includes at least two of bisphenol A propylene glycol dimethacrylate, triethylene glycol dimethacrylate, methacrylate and urethane dimethacrylate; Optionally, the acrylic monomer resin mixture is triethylene glycol dimethacrylate and urethane dimethacrylate; Optionally, the mass ratio of the triethylene glycol dimethacrylate to the urethane dimethacrylate is (7-3): (3-7); Optionally, the initiator is selected from peroxides and / or azo compounds; Optionally, the peroxide comprises benzoyl peroxide; Optionally, the content of the initiator is 0.1wt% to 0.5wt% of the acrylic monomer resin mixture; Optionally, the warm isostatic pressing parameters include a temperature of 30°C to 60°C and a pressure of 50MPa to 150MPa; Optionally, the penetration time is 1 h to 3 h.
5. The preparation method according to claim 1 or 2, characterized in that: The ceramic body infiltrated with resin is cured in a resin matrix without an initiator by warm isostatic pressing; Optionally, the resin matrix without initiator is an acrylic monomer resin mixture as defined in claim 4; Optionally, the warm isostatic pressing parameters include a temperature of 100° C. to 150° C. and a pressure of 80 MPa to 200 MPa.
6. The preparation method according to claim 1 or 2, characterized in that: The particle size of the barium glass that has not been silanized ranges from 0.1 μm to 3 μm, the particle size is normally distributed, and the average particle size is from 0.6 μm to 0.8 μm.
7. The preparation method according to claim 1 or 2, characterized in that: The amount of the adhesive added is 2wt% to 9wt% of the ceramic material; Optionally, the adhesive comprises polyethylene glycol; Optionally, the solvent is acidic deionized water.
8. The preparation method according to claim 1 or 2, characterized in that: Dry pressing includes compression molding and cold isostatic pressing; Optionally, the compression molding pressure is 6MPa to 12MPa; Optionally, the pressure of cold isostatic pressing is 160 MPa to 220 MPa.
9. The preparation method according to claim 1 or 2, characterized in that: The mixing methods include ball milling; Optionally, after mixing, the method further includes drying the obtained slurry and grinding it into powder.
10. Dental resin-infiltrated ceramics prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Resin permeable silicate ceramic composite material and preparation method thereof
CN120717806A